PENGARUH KOMBINASI CMC DAN GUM ARAB TERHADAP MUTU SENSORI VELVA UBI JALAR UNGU - Lestari, Sri Dewi; Ayu, Dewi Fortuna; Rahmayuni, Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to determine the effect of combination of CMC and arabic gum on the sensory quality of purple sweet potato velva. This research used a Completely Randomized Design experiment with five treatments and   three replications. The parameters were S1 (CMC andarabic gum = 1 : 0),                 S2 (CMC andarabic gum = 2 : 1), S3 (CMC andarabic gum = 1 : 1),                  S4 (CMC andarabic gum = 1 : 2), and S5 (CMC andarabic gum = 0 : 2).  The data obtained were analyzed statistically using Analysis of Variance (ANOVA) and followed by Duncan’s New Multiple Range Test (DNMRT) test at 5% levels.  The research observed were sensory value on descriptive and hedonic test.  The result of analysis of variance showed that the combination of CMC and arabic gum has significantly value on descriptive and hedonic test such as texture, but did not significantly affectedsensory value descriptive and hedonic colour, flavour,and taste. The best treatment of purple sweet potato velva from this research wasS4 which had descriptive test assessment showed that the velva had purple color (4.26), purple sweet potato flavour (4.23), sweet taste (4.09), and soft texture (4.71).  Overall assessment of hedonic test on purple sweet potato velva was preferred by the panellists. Keywords: Arabic gum, CMC, purple sweet potato, and velva.